DALUARSANYA HAK PENUNTUTAN PADA PERKARA PIDANA PEMALSUAN TANDA TANGAN PERMOHONAN PENETAPAN AHLI WARIS MENURUT PASAL78 KUHP - Ajehar Ajehar (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT The Code of Penal (Penal Code) has set a certain period of time on the subject of prosecution, may be expired by law. The provisions in the Criminal Code article 78 is actually set up for criminal prosecution expired rights, but it should also be linked to the right to run a penalty. Time of death of the right to run a longer sentence than the death the right of criminal prosecution because the accused is certain errors. The criminal act of forgery as governed by Article 263 Penal Code was actually a criminal act that should be done deliberately up to declare a person charged with a criminal act of forgery was proven, the prosecutors and judges must prove the existence of the will of the defendant to act in a false or falsified letter. The intent of the defendants to use their own letter as the letter is genuine and not faked or to make any other person a letter that he created artificially, required the knowledge of the defendants that of the use of the letter that he has made is false or that he trumped it can cause harm.